OCCURRENCE AND DISTRIBUTION OF TETRAETHER MEMBRANE LIPIDS IN SOILS: IMPLICATIONS FOR THE USE OF THE TEX86 PROXY AND THE BIT INDEX - Weijers J.W.H.; Schouten S.; Damsté J.S.S.; Spaargaren O.C. (My University, 2006)
A diverse collection of globally distributed soil samples was analyzed for its glycerol dialkyl glycerol tetraether (GDGT) membrane lipid content. Branched GDGTs, derived from anaerobic soil bacteria, were the most dominant and were found in all soils. Isoprenoid GDGTs, membrane lipids of Archaea, were also present, although in considerably lower concentration. Crenarchaeol, a specific isoprenoid membrane lipid of the non-thermophilic Crenarchaeota, was also regularly detected and its abundance might be related to soil pH. The detection of crenarchaeol in nearly all of the samples is the first report of this type of GDGT membrane lipid in soils and is in agreement with molecular ecological studies, confirming the widespread occurrence of non-thermophilic Crenarchaeota in the terrestrial realm. The fluvial transport of crenarchaeol and other isoprenoid GDGTs to marine and lacustrine environments could possibly bias the BIT index, a ratio between branched GDGTs and crenarchaeol used to determine relative terrestrial organic matter (TOM) input. However, as crenarchaeol in soils is only present in low concentration compared to branched GDGTs, no large effect is expected for the BIT index. The fluvial input of terrestrially derived isoprenoid GDGTs could also bias the TEX86, a proxy used to determine palaeo surface temperatures in marine and lacustrine settings and based on the ratio of cyclopentane-containing isoprenoid GDGTs in marine and lacustrine Crenarchaeota. Indeed, it is shown that a substantial bias in TEX86-reconstructed sea and lake surface temperatures can occur if TOM input is high, e.g. near large river outflows. © 2006 Elsevier Ltd. All rights reserved.